Proceedings of the Annual Civic Education Conference (ACEC 2018) 2018
DOI: 10.2991/acec-18.2018.60
|View full text |Cite
|
Sign up to set email alerts
|

Civic Education and Student Responses to Global Issue

Abstract: This study is based on thinking that Civic Education has role in building students' global insight and awareness. Through Civic Education, students will aware of their role and responsibility toward global issue. One of the most effective ways to improve the world and help people inside it is through social movement. Therefore, Civic Education has role to encourage students in understanding complex global issue and deciding what step and action done as the form of response to global challenge. This study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…First, Civic Education Learning in Higher Education is still dominated by strengthening knowledge (civic knowledge), and paying less attention to aspects of attitude (civic knowledge) and skills (civic skills). This is in line with the results of research conducted by (Dharma, Sapriya, Winataputra, & Komalasari, 2018) which found that Citizenship Education Learning in Higher Education is still carried out verbally so that it has not touched the strengthening of citizens' attitudes and skills. The results also state that Citizenship Education not only strengthens citizens' knowledge, but also helps students gain new experiences to be actively involved in responding to global issues, including environmental issues (Dharma, Sapriya, Winataputra, & Komalasari, 2018).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, Civic Education Learning in Higher Education is still dominated by strengthening knowledge (civic knowledge), and paying less attention to aspects of attitude (civic knowledge) and skills (civic skills). This is in line with the results of research conducted by (Dharma, Sapriya, Winataputra, & Komalasari, 2018) which found that Citizenship Education Learning in Higher Education is still carried out verbally so that it has not touched the strengthening of citizens' attitudes and skills. The results also state that Citizenship Education not only strengthens citizens' knowledge, but also helps students gain new experiences to be actively involved in responding to global issues, including environmental issues (Dharma, Sapriya, Winataputra, & Komalasari, 2018).…”
Section: Introductionsupporting
confidence: 89%
“…This is in line with the results of research conducted by (Dharma, Sapriya, Winataputra, & Komalasari, 2018) which found that Citizenship Education Learning in Higher Education is still carried out verbally so that it has not touched the strengthening of citizens' attitudes and skills. The results also state that Citizenship Education not only strengthens citizens' knowledge, but also helps students gain new experiences to be actively involved in responding to global issues, including environmental issues (Dharma, Sapriya, Winataputra, & Komalasari, 2018). Furthermore, according to (Hidayah, Ulfah, & Suyitno, 2019) that Civic Education learning in Higher Education must provide learning experiences to students through various learning approaches such as contextual approaches, constructivism and open-ended.…”
Section: Introductionsupporting
confidence: 89%
“…Furthermore, by teaching civic education, social integration and social cohesiveness among students of different ethnic and racial backgrounds can be achieved (Claes et al, 2009). Furthermore, civic education can resolve global terrorism, violence, racial and ethnic prejudice, and discrimination (Dharma et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the results of research conducted by [5] on Citizenship Education and Student Social Movements in responding to global issues at Medan State University. The results show that Citizenship Education learning at Medan State University still does not accommodate the development of student global awareness and responsibility.…”
Section: Introductionmentioning
confidence: 99%